Why Dogs Stopped Flying: Poems - Brewer, Ken W. (Utah State University, University Libraries, 2006)
The solid rightness of image after image in Ken Brewer's poetry was never better than in Why Dogs Stopped Flying. His familiar style is plain-spoken, his humor reliable and self-ironic. Yet, in this collection perhaps more than in his earlier work, the particularity of the poet's insight into the physical world--and the warmth of his affection for it--combine to create an unexpected transcendence. Beasts and bodies are transformed in his lines, and our dim, unremarkable lives on this shadowed earth become somehow more luminous--small suns opening in the dark, small words to the moon.